Keragaman pangan, pola asuh makan dan kejadian stunting pada balita usia 24-59 bulan - Widyaningsih, Novita Nining; Kusnandar, Kusnandar; Anantanyu, Sapja (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background: Stunting is a chronic nutritional problem that occurs due to lack of nutrient intake over a long period of time, causing growth disturbances which are marked by an appropriate height for age. The incidence of stunting in toddlers is influenced by the low access to food both in terms of quantity and quality. In addition, it is also influenced by the feeding parenting from the mother, particularly in the feeding practice of the children.Objective: To determine the relationship between food diversity and feeding practice with the incidence of stunting in toddlers aged 24-59 months in Bayat Sub-district, Klaten Regency.Method: The study design used was a cross-sectional study. The study was conducted in Bayat Sub-district, Klaten Regency, with a total subject of 100 toddlers aged 24-59 months. The simple random sampling technique was used for sampling. Birth weight and birth length data as seen from KMS book. The food diversity was measured using IDDS (Individual Dietary Diversity Score) questionnaire and feeding practise was obtained through interviews measured using structured questionnaire. The data was then analyzed using bivariate (chi square) and multivariate (logistic regression) analysis.Results: This study showed that the 41% of toddlers aged 24-59 months are stunted. Chi square test showed that there were a relationship between birth length, feeding practice and food diversity with stunting (p â‰¤ 0.05). The result of multivariate analysis showed that there was a relationship between food diversity with stunting (p= 0,029, OR=3,213, 95% Cl: 1,123-9,189).Conclusion: There is a relationship between birth length, feeding practice, and food diversity with stunting. The most dominant risk factor for stunting was food diversity.